Utilization of unmanned aerial vehicle (UAV) in dam disaster management: evacuation planning - Mamat, Ahmad Fadhli; Mohd. Hussain, Mohd. Ramzi; Tukiman, Izawati; Rabe, Noor Suzilawati; Muda, Rahsidi Sabri; Md Amin, Mohamad Faiq (Academia Industry Networks, 2020)
With the increase of world population and eventually the increase in populated areas at disaster prone areas, a disaster that previously would have been low in risk, is getting more catastrophic each year. Various counter measures are being undertaken to ensure that the impact of a disaster is being well mitigated to ensure the safety and sustainability of the population at risk. This paper will be looking at more depth on the use of Unmanned Aerial Vehicle (UAV) in emergency preparedness, particularly towards the identification effective evacuation routes, in order for the targeted population to safely reach the identified safe haven.